Effects of injectable anaesthetics on responses to L-glutamate and on spontaneous synaptic activity in lamprey reticulo-spinal neurones. - Cullen, K. D. (Nature Publishing Group, 1984)
Intracellular recordings were made from reticulo-spinal cells in the medulla of lamprey ammocoetes; potential changes in response to iontophoretically applied L-glutamate were measured before, during and after the preparation was superfused with anaesthetic solutions. Of the anaesthetics pentobarbitone, ketamine, alphaxalone/alphadolone (Saffan) and metomidate, only pentobarbitone (greater than 10 microM) had a consistent dose-related depressant effect on glutamate responses. Spontaneous excitatory postsynaptic potentials (e.p.s.ps) and inhibitory postsynaptic potentials (i.p.s.ps) were diminished in frequency by high concentrations (1 mM) of all anaesthetics. Anaesthetic concentrations of all drugs also reduced i.p.s.ps; for e.p.s.ps this was true of pentobarbitone (100 microM) immediately, and of ketamine (370 microM) and alphaxalone (10-30 microM) after a transitory increase in activity. Consideration of the results in the light of previous observations on inhibitory responses suggests a basis for some of the excitatory side effects of these compounds, assuming that the equivalent mammalian cells are similarly affected.